Variability of the caprine whey protein genes and their association with milk yield, composition and renneting properties in the Sarda breed: 2. The BLG gene. Issue 4 (16th September 2015) - Dettori, Maria Luisa; Pazzola, Michele; Pira, Emanuela; Puggioni, Ornella; Vacca, Giuseppe Massimo
Abstract : The variability of the promoter region and the 3′UTR (exon-7) of the BLG gene, encoding the β-lactoglobulin, was investigated by sequencing in 263 lactating Sarda goats in order to assess its association with milk traits. Milk traits included: milk yield, fat, total protein and lactose content, pH, daily fat and protein yield (DFPY), freezing point, milk energy, somatic cell count, total microbial mesophilic count, rennet coagulation time (RCT), curd firming rate (k20) and curd firmness (a30). A total of 7 polymorphic sites were detected and the sequence analysed was given accession number KM817769. Only three SNPs (c.−381C>T, c.−323C>T and c.*420C>A) had minor allele frequency higher than 0·05. The effects of farm, stage of lactation and the interaction farm × stage of lactation significantly influenced all the milk traits ( P < 0·01, P < 0·001) except for lactose content and SCS, which were not affected by the farm, and RCT and k20, which were not affected by the stage of lactation. The BLG gene polymorphism influenced milk yield and DFPY, in relation to SNPs c.−381C>T and c.*420C>A ( P < 0·01 and P < 0·05). All three SNPs affected milk pH, and this association was highly significant at c.−381C>T ( P < 0·001). The c.−381TT homozygous goats showed lower pH, RCT and k20 than c.−381CT ( P < 0·05). In conclusion the polymorphism of the goat BLG gene did not affect the total protein content of the Sarda goat milk, and only weakly influenced RCT and k20. On the other hand, an interesting effect on milk yields and DFPY emerged in two SNPs. This information might be useful in dairy goat breeding programs.